Association of Persistent Minimal Residual Disease with Poor Outcomes of Patients with Acute Myeloid Leukemia Undergoing Allogeneic Hematopoietic Stem Cell Transplantation - Jing Liu; Xiao-Su Zhao; Yan-Rong Liu; Lan-Ping Xu; Xiao-Hui Zhang; Huan Chen; Yu-Hong Chen; Feng-Rong Wang; Wei Han; Yu-Qian Sun; Chen-Hua Yan; Fei-Fei Tang; et al. (Chinese Medical Journal, 2018)
Background: Several studies have shown that detection of minimal residual disease (MRD) in acute myeloid leukemia (AML) is an independent prognostic factor. This study aimed to evaluate the significance of dynamic MRD pretransplantation on outcome of AML patients receiving allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods: We retrospectively analyzed 145 consecutive AML patients undergoing allo-HSCT in complete remission status between June 2013 and June 2016. MRD was determined with multiparameter flow cytometry after the first and second courses of chemotherapy and pre-HSCT. Results: In matched sibling donor transplantation (MSDT) settings, patients with positive MRD had higher cumulative incidence of relapse (CIR) than those without MRD after the first (32.3 ± 9.7% vs. 7.7 ± 3.1%, χ2 = 3.661, P = 0.055) or second course of chemotherapy (57.1 ± 3.6% vs. 12.5 ± 2.7%, χ2 = 8.759, P = 0.003) or pre-HSCT (50.0 ± 9.7% vs. 23.0 ± 3.2%, χ2 = 5.547, P = 0.019). In haploidentical SCT (haplo-SCT) settings, the MRD status at those timepoints had no significant impact on clinical outcomes. However, patients with persistent positive MRD from chemotherapy to pre-HSCT had higher CIR than those without persistent positive MRD both in MSDT and haplo-SCT settings. Patients with persistent positive MRD underwent MSDT had the highest relapse incidence, followed by those with persistent positive MRD underwent haplo-SCT, those without persistent MRD underwent haplo-SCT, and those without persistent MRD underwent MSDT (66.7 ± 9.2% vs. 38.5 ± 6.0% vs. 18.8 ± 8.7% vs. 12.0 ± 1.0%, χ2 = 20.763, P < 0.001). Multivariate analysis showed that persistent positive MRD before transplantation was associated with higher CIR (hazard ratio [HR] = 1.69, 95% confidence interval [CI]: 1.200–2.382, P = 0.003), worse leukemia-free survival (HR = 1.812, 95% CI: 1.168–2.812, P = 0.008), and overall survival (HR = 2.354, 95% CI: 1.528–3.627, P < 0.001). Conclusion: Our results suggest that persistent positive MRD before transplantation, rather than positive MRD at single timepoint, could predict poor outcome both in MSDT and haplo-SCT settings.